Faktor-Faktor Yang Mempengaruhi Cash Holding Perusahaan Manufaktur Pada Tahun 2017-2019 - Angelica; Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to determined the effect of the leverage, profitability, firm size, net working capital, and capital expenditure on cash holding of manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 35 companies. Data processing techniques using multiple regression analysis that helped by EViews 11 SV software to test the hypothesis. The results of this study indicate that leverage, profitability, firm size, and capital expenditure had no effect on cash holding while net working capital had negative and significant effect on cash holding.